2023
DOI: 10.1021/acsomega.3c00056
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Role of ELOVL in Neurological Diseases

Abstract: Fatty acids play an important role in controlling the energy balance of mammals. De novo lipogenesis also generates a significant amount of lipids that are endogenously produced in addition to their ingestion. Fatty acid elongation beyond 16 carbons (palmitic acid), which can lead to the production of very long chain fatty acids (VLCFA), can be caused by the rate-limiting condensation process. Seven elongases, ELOVL1–7, have been identified in mammals and each has a unique substrate specificity. Researchers ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…The lack of replications of SARS-CoV-2 in the neurons is perhaps due to the decreased expression of ELOVL1 in infected neurons (Figure 2C) as a compensatory mechanism to evade the virus. Furthermore, ELOVL1 deficiency can lead to neurological defects such as hypomyelination [103] that would render the neuronal firing slow and less efficient and, therefore, could explain the fatigue experienced by COVID-19 patients, particularly in long COVID. Our proteomic profiling of infected neurons also revealed downregulation of HMGCS1 (Hydroxy-Methylglutaryl-CoA Synthase), which is involved in cholesterol biosynthesis and was noted to be downregulated in multiple cell lines infected with SARS-CoV-2 [104].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of replications of SARS-CoV-2 in the neurons is perhaps due to the decreased expression of ELOVL1 in infected neurons (Figure 2C) as a compensatory mechanism to evade the virus. Furthermore, ELOVL1 deficiency can lead to neurological defects such as hypomyelination [103] that would render the neuronal firing slow and less efficient and, therefore, could explain the fatigue experienced by COVID-19 patients, particularly in long COVID. Our proteomic profiling of infected neurons also revealed downregulation of HMGCS1 (Hydroxy-Methylglutaryl-CoA Synthase), which is involved in cholesterol biosynthesis and was noted to be downregulated in multiple cell lines infected with SARS-CoV-2 [104].…”
Section: Discussionmentioning
confidence: 99%
“…In astrocytes, Elovl mediates the production of long-chain saturated fatty acids, and Smad2 is associated with autophagy. 60 Therefore, only the following hypothesis is plausible: miR-124-3p/Smad2 axismediated autophagy and/or ER stress play roles in astrocyte activation. We also anticipated validating a hypothesis based on as much literature as possible.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Since miR-124-3p targets a wide range of molecules, the search was conducted for downstream targets of circHIPK2/miR-124-3p that are involved in the activation of A1 astrocytes. First, by searching the literature, we identified two genes, Elovl and Smad2, that were associated with astrocytes. , Second, studies have shown one mechanism that miR-124-3p inhibits astrocyte activation or switches the astrocytes into induced neurons, wherein autophagy, ER stress, PI3K/AKT/NF-κB, and ARE-mediated mRNA decay signals are considered to be involved. ,, To establish associations among miR-124-3p, astrocyte activation, and potential target genes, we performed a literature review of the study topic. In astrocytes, Elovl mediates the production of long-chain saturated fatty acids, and Smad2 is associated with autophagy .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations